Intra-industry information transfer in emerging markets: Evidence from China - Liu, Beibei; Tan, Keqi; Wong, Sonia M.L.; Yip, Rita W.Y. (Journal of Banking & Finance, 2022)
This study examines intra-industry information transfer in the emerging market of China, where financial and market institutions are underdeveloped and the majority of investors are inexperienced individual investors. In an analysis of the management earnings forecasts of publicly listed firms, we find that investors in China transfer information between peer firms, with a stronger transfer when earnings forecasts are more accurate and credible, and when the investors of non-announcing firms are more sophisticated. We also find that the non–market-based resource allocation and entry restrictions in China discourage intra-industry information transfer between firms. Overall, our results suggest that intra-industry information transfer in China is constrained by institutional barriers. Reforms aimed at removing these barriers can help enhance these markets’ stock price efficiency. Our results provide policy implications to other emerging markets with institutional environments similar to China.